In vitro bioactivities of Tabernaemontana divaricata andTabernaemontana divaricata ‘Flore Pleno’ variant / Muhammad Nazzim Muaz Abdul Halim - Muhammad Nazzim Muaz, Abdul Halim (2022)
Two Tabernaemontana species, Tabernaemontana divaricata (TD) and Tabernaemontana divaricata ‘Flore Pleno’ variant (TDF) were chosen to be studied for their bioactivities in relation to wound healing properties. Methanol (M) and aqueous (A) extracts of these Tabernaemontana species were used in this study for wound healing potential assessment on adult normal human dermal fibroblasts (HDFa) cells, total phenolic contents (TPC), antioxidant potential, protective effects against hydrogen peroxide (H2O2) and anti-inflammatory properties by means of nitric oxide (NO) production from RAW264.7 murine macrophage cells. TD-A extract reported the highest wound closure (58.50%) followed by TDF-A extract (53.54%) with the highest total phenolic content (31.96 mg GAE/g). The free radical scavenging activities carried out by ABTS and DPPH assay showed that TDF-A extract was able to exhibit the highest antioxidant values at IC50 = 1.11 μg/ml and IC50 = 2.44 μg/ml respectively compared to the other extracts. Reducing activity on TDF-A extract assessed by FRAP assay also reported high value of [18.07 mM Fe (II)/g] with other extracts. Pre-treatment and post-treatment assessment showed at 25 μg/ml of TDF-M extract concentration were able to provide protectivity towards HDFa cells against H2O2 with cell viability at 93.92% and 89.69% respectively. At 500 μg/ml of TD-A and TDF-A extract concentration, the extracts were able to inhibit NO production by RAW264.7 murine macrophage cells at 5.22 μM and 5.11 μM respectively. Based on these findings, it is shown the two Tabernaemontana species studied exhibit multiple bioactivities that may contribute to the wound healing process in general. Keywords: